Fishermen empowerment and marine conservation based on TURING in tackling ghost fishing - Sholichin Adji Saputro; Kukuh Eko Prihantoko; Rafi Zulmy Saputra; Revinda Aradea Adat; Nasheila Mutia Zanjabila (Universitas Pendidikan Indonesia, 2025)
The natural resources potential of Samas Beach has led to the use of fishing gear. Fishing nets made of nylon take a very long time to decompose. Ghost fishing is a phenomenon where fish are caught by nets that have been lost or abandoned at sea. Ghost fishing has a profound impact on the marine environment. This impact is not only ecological, economic, and social, but also particularly affects small-scale fishermen who experience a decline in income due to reduced fish stocks. The abandoned fishing gear at Samas Beach is a result of the gear's deterioration. Based on the issues and events occurring at the location, the TURING Team from the University of Diponegoro PKM-PM initiated an innovation in the form of a net collection device called TURING. The methods used include interviews and data analysis. The implementation of TURING is expected to benefit coastal communities due to its ease of implementation, readily available raw materials, and cost-effective efficiency. The objective of the PKM-PM initiative is to provide guidance, training, and empowerment to the coastal communities of Samas Beach in addressing ghost fishing and sea turtle conservation through the development of TURING. Abstrak Potensi sumber daya alam di Pantai Samas menimbulkan aktivitas penggunaan alat tangkap. Jaring ikan yang terbuat dari bahan nilon sangat lama untuk menguraikannnya. Ghost fishing merupakan suatu keadaan ikan tertangkap oleh jaring yang sudah hilang di perairan laut. Ghost fishing memiliki dampak yang serius pada lingkungan laut. Dampak ini tidak hanya bersifat ekologis, ekonomis dan sosial, terutama bagi nelayan kecil yang mengalami penurunan pendapatan akibat berkurangnya stok ikan. Alat tangkap yang terbengkalai di Pantai Samas disebabkan oleh faktor rusaknya alat tangkap. Berdasarkan permasalahan dan peristiwa yang terjadi di lokasi, Tim TURING Universitas Diponegoro PKM-PM berinisiatif melalui sebuah inovasi alat penampung jaring dengan sebutan TURING. Metode yang diguanakan yaitu menggunakan metode wawacara dan analisis data. Penerapan TURING diharapkan dapat bermanfaat bagi masyarakat pesisir dikarenakan konsep yang sangat mudah diimplementasi oleh masyarakat, bahan baku yang mudah ditemukan serta efisiensi biaya yang lebih terjangkau. Tujuan dari gagasan PKM-PM adalah melakukan pendampingan, pelatihan, dan pemberdayaan masyarakat pesisir Pantai Samas dalam upaya mengatasi ghost fishing dan konservasi penyu dengan membuat TURING. Kata Kunci: alat memancing; ghost fishing; pemberdayaan nelayan; TURING